The Impact of the Covid-19 Pandemic on the Online Learning Process of Students in Junior High School - Kamaruddin, Kamaruddin; Patimbangi, Andi; Ismail, Ismail; Armita, Devi (Jurnal Pendidikan dan Pengajaran, 2021)
Online learning is one of the best solutions in the world of education to suppress the spread of the Covid-19 virus in the world of education, it's just that the implementation of online learning is not fully able to run optimally and causes various kinds of impacts in the learning process, including learning for junior high school students. This study aims to analyze the impacts felt by junior high school students in the online learning process during the covid-19 pandemic. This research is a type of descriptive research using a library research model. The subjects in this study were articles and news related to the research topic, so the data collection technique used was to carry out a documentation study which was then analyzed using qualitative descriptive data analysis using 4 stages of analysis, namely data collection, data reduction, data display and, conclusion. The results in this study indicate that the impact of online learning during the pandemic is student learning, experiencing interference in assessments, cancellation of assessments, opportunities to get jobs after graduating from education, cancellation of public assessments for qualifications in job selection. So it can be concluded that there are various kinds of impacts that arise as a result of the online learning process, where negative impacts should be immediately sought to solve problems so that these impacts do not spread to other components of education.